New approaches toward anti-Rhipicephalus (Boophilus) microplus tick vaccine - Parizi,Luís Fernando (2009)
The tick Rhipicephalus (Boophilus) microplus (formerly Boophilus microplus) is the major ectoparasite affecting livestock in America, Asia, Africa, and Oceania. Conventional tick control is based on the use of acaricides but immunization of bovines with tick gut proteins induces only a partial protective immune response. Based on this information, distinct research groups have explored the possibility of protecting the animals by inducing an immune response against other tick proteins. However, the antigens so far described do not induce the necessary protection for suppressing the use of acaricides. Currently, several groups are engaged in identifying new tick proteins to be used as targets for the development of new vaccines. This approach focuses on the enhancement of the immunogenicity of antigens already tested by incorporating new adjuvants or formulations and by searching for new antigens. This paper reviews the work done by Brazilian researchers to develop a vaccine against this tick.